سياسات إصلاح النظام الجبائي -دراسة حالة الجزائر - شيحي, حسين; لعلى, عتيق (جامعة الوادي - University of Eloued, 2022)
يعد إصلاح النظام الجبائي من الخطوات الأساسية للإصلاح الاقتصادي بحيث يدخل ضمن الهيكل المالي للاقتصاد ومركزا حيويا في تعبئة المدخرات، وتمويل التنمية ، كما أثبتت التطورات الاقتصادية في الدول النامية التي تسعى جاهدة لتحقيق التنمية، إلى أهمية دور النظام الجبائي في تمويل التنمية الاقتصادية والمحافظة على الاستقرار الاقتصادي. ومن اجل أن يكون هذا الاصلاح فعالا ويؤدي دوره في احسن وجه لابد وان يعتمد على عدة سياسات وطرق يجب اتباعها حين القيام بهذه بعملية , ولكل نظام له خصوصيته ومميزاته التى يختلف به عن غيره فلذا لابد من إتباع الطريقة المثلى والاحسن مع مراعات خصوصية كل نظام لي دولة كانت . وتعتبر الجزائر كغيرها من الدول تسعى جاهدة من خلال عمليات الاصلاح المستمرة لنظام الجبائي , الى محاولة تحقيق أهدافه ومن خلال دراستنا التطبيقة توصلنا الى أن تم قطع شوطا هاما لتحقيق والوصول الى أهداف الاصلاح الجبائي خاصة من خلال أهم التعديلات التى جاء بها قانون المالية لسنة 2022 . The reform of tax system is one of the economic reform basic step’s, so that it falls within the financial economy structure and a vital role in mobilizing savings, financing for development, as demonstrated by the economic developments in developing countries, which are striving to achieve development of the importance role of the tax system to finance economic development and maintain economic stability.n order for this reform to be effective and perform its role in the best way, it must depend on several policies and methods that must be followed when carrying out this process. She was. Algeria, like other countries, is striving, through continuous reform of the tax system, to try to achieve its goalsThrough our applied study, we concluded that an important stride has been made to achieve and reach the goals of fiscal reform, especially through the most important amendments that came in the Finance Law for the year 2022
Fiscal Reform System Policies: Algeria case study
مقال
Keywords: الاصلاح الضريبي ; النظام الجبائي ; الضريبة ; قانون المالية 2022 ; السياسات الضريبية